INFORMATION LITERACY DISCIPLINE NECESSARY FOR THE TRAINING OF THE ARCHIVIST? - Furtado, Renata Lira [UNESP]; Belluzzo, Regina Célia Baptista [UNESP]; Vitoriano, Marcia Cristina de Carvalho Pazin [UNESP] (My University, 2019)
It aims to identify elements related to information literacy in the curriculum guidelines and pedagogical projects of undergraduate courses in Brazilian archival science. The results evidenced that the discipline precepts pass through the documents implicitly, however, it is necessary to identify other evidences that consolidate its relevance to the archival training.
COMPETÊNCIA EM INFORMAÇÃO DISCIPLINA NECESSÁRIA À FORMAÇÃO DO ARQUIVISTA?
Keywords: archival science; information literacy; professional qualification